PENERAPAN METODE ABC TERHADAP PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA UD. MAYONG SARI PROBOLINGGO - Junaidi Junaidi (CAPITAL: Jurnal Ekonomi dan Manajemen, 2019)
U.D Mayong Sari Kabupaten Probolinggo is a business engaged in the manufacture of food especially bread which has existed for 25 years was established on augst 18 1991 by Mr. Mayong Efendi. UD. Mayong Sari previously not using the ABC method in classifying thu use of raw materias. ABC method of inventory control is a technique by observing groups of goods according to the level of importance of each group of goods. Group items in ABC Analisis based on the total value of sales in a year. The purpose of this study was to determine the classification or types of raw materials what is included in group A, B, C in the ABC analysis. with ABC method can be known raw materials with the highest invesment, medium, and low turnover of the raw marerial based on usage. Type of row material product umit is made up of nine types of components. Based on the results if the data then these components can be categorized in three catagories: category A, category B, and category C. Of the nin types of componentse calculated, based on Table 3, then those in category A are 2 types of components ie flour and butter because the cumulative percentage of absorption of funds is less than or equal to 80%, whereas the cumulative percentage item items of goods less than or more than 20%, category B amounts to 2 types of components ie sugar and beans Both types of components because the cumulative percentage item type of goods less than or more than 30%,and 5 types of components included in category C, namely Stem Milk, Chocolate bar, Egg, Strawbery Jam and Banana, the five components are classified C class which has a cumulative percentage item type of goods more than 50%.. Wherein category A class is the most importand raw material in the production process, the control needs to be looked at more.Keywords: control supplies, ABC method, Inventory